Nationalism and Islam in Religious Learning: Optimization of Insan Kamil Character Building - Yulia Rahman; Abdul Rahman Ritonga (Islam Realitas: Journal of Islamic and Social Studies, 2021)
This study aims to explain that religious learning held in public schools is able to instill the values of nationalism and Islam, thus forming the character of students of insan kamil. This theory refutes the opinion which states that religious education creates civic conflict and cannot be a complement to civic education. This research complements several previous studies by adding research on Rohis (spiritual learning program) as part of religious learning in public schools. The research method used is a mix-method research with qualitative analysis and a sociological approach. The conclusion of this study is that religious learning, both in terms of material and methodology, is able to instill the value of religious-nationalism. The internalization of the values of nationalism-religion is applied in PAI (Islamic) learning in the classroom which is guided by teachers, and religious learning in Rohis which is guided by mentorsPenelitian ini bertujuan untuk menjelaskan bahwa pembelajaran agama yang diselenggarakan di sekolah umum mampu menanamkan nilai-nilai nasionalisme dan Islam, sehingga membentuk karakter peserta didik yang insan kamil. Teori ini membantah pendapat yang menyatakan bahwa pendidikan agama berpotensi melahirkan konflik kewarganegaraan dan tidak mampu menjadi komplemen pendidikan kewarganegaraan. Penelitian ini melengkapi beberapa penelitian terdahulu dengan menambahkan penelitian pada pembelajaran Rohis sebagai bagian dari pembelajaran agama di sekolah umum. Metode penelitian yang digunakan adalah mix-method research dengan analisis kualitatif dan pendekatan sosiologi pendidikan. Kesimpulan penelitian ini adalah bahwa pembelajaran agama, baik dari segi materi dan metodologinya mampu menanamkan nilai nasionalisme-religius. Internalisasi nilai nasionalisme-religius ini diterapkan dalam pembelajaran PAI di kelas yang dibimbing oleh guru dan pembelajaran agama di Rohis yang dibimbing oleh para mentor